Clinicopathological Characteristics and Prognosis for Survival after Enucleation of Uveal Melanoma in Chinese Patients: Long-term Follow-up. (4th May 2017) - Yue, Han; Qian, Jiang; Yuan, Yifei; Zhang, Rui; Bi, Yingwen; Meng, Fengxi; Xuan, Yi
ABSTRACT: Purpose : To summarize the clinicopathological characteristics and prognosis of uveal melanoma (UM) after enucleation in Chinese patients. Methods : Between 2003 and 2012, a series of 171 patients with UM received enucleation at the Eye & ENT Hospital of Fudan University in Shanghai. Patient clinical information was collected. Pathological examination and BAP1 staining of the enucleated eyes were conducted. Univariate and multivariate Cox proportional hazard regressions were conducted to determine the risk factors, and the survival rates were calculated and compared. Results : The study included 83 (49%) men and 88 (51%) women, with a mean age of 48.6 years. The mean largest basal tumor diameter and mean largest tumor thickness were 11.8 and 8.6 mm, respectively. Ciliary body involvement was observed in 19 tumors (11%). Spindle and nonspindle patterns were observed in 100 (58%) and 71 eyes (42%), respectively. Extrascleral extension was observed in three eyes (2%). BAP1 staining was negative in 34% (53/156) of all tumors and 53% (19/36) of the cases with melanoma-related metastasis. The mean follow-up period was 63.4 months for all patients with the exception of 11 patients, who were excluded because they were lost during follow-up. A large basal tumor diameter, ciliary body involvement, nonspindle cell type, extrascleral extension, and negative BAP1 staining were associated with a worse prognosis. The survival curves significantly differed between the BAP1-negative and BAP1-positive groups ( P = 0.004). According to Kaplan–Meier analysis, the 5- and 10-year metastasis-free survival rates were 80% and 70%, respectively. Conclusions : A large basal tumor diameter, ciliary body involvement, nonspindle cell type, extrascleral extension, and negative BAP1 staining may be risk factors for the prediction of the UM prognosis. A younger age at diagnosis and a similar prognosis between genders may be unique features in Asian patients compared to the Caucasian population.